Salivary glutamate is elevated in individuals with chronic migraine. (July 2018) - Nam, Ji Hye; Lee, Hun Seok; Kim, Jiyoung; Kim, Jinmi; Chu, Min Kyung
Background: Glutamate has been implicated in migraine pathogenesis, and is elevated in the plasma, cerebrospinal fluid, and saliva in migraineurs. However, no comparison of glutamate levels among chronic migraine, episodic migraine and controls has been reported. The aim is to compare salivary glutamate levels of individuals with chronic migraine with those of individuals with episodic migraine and healthy controls. Methods: We investigated salivary glutamate level of 46 women with chronic migraine, 50 women with episodic migraine, and 19 healthy controls via enzyme linked immunosorbent assay. Results: The salivary glutamate level of the chronic migraine group (median and interquartile range, 20.47 [15.27–30.15] pmol/mg total protein) was significantly higher than those of the episodic migraine (16.17 [12.81–20.15] pmol/mg total protein, p  = 0.008) and control (12.18 [9.40–16.24] pmol/mg total protein, p  = 0.001) groups. The salivary glutamate level of the episodic migraine group was marginally elevated from that of the control group (post hoc p  = 0.016). Thresholds of 16.58 and 17.94 pmol/mg total protein optimize the sensitivity and specificity to differentiate chronic migraine participants from healthy controls and episodic migraine participants, respectively. Conclusions: Salivary glutamate level was elevated in chronic migraine participants. These data suggest that salivary glutamate level could be an indicator of CM